SQSTM1/p62 interacts with FKBP38 and regulates cell cycle in Cashmere goat foetal fibroblasts. Issue 1 (1st January 2018) - He, Qiburi; Wang, Yanfeng; Zhao, Keyu; Binderiya, Uyanga; Bao, Lili; Zhao, Pingping; Yan, Dandan; Hao, Huifang; Guo, Xudong; Wang, Zhigang
ABSTRACT: SQSTM1 (sequestosome 1, also known as p62) is a multifunctional scaffold protein implicated in diverse cell physiology processes, such as autophagy, cell signalling, and protein turnover. FKBP38 (FK506-binding protein 38) is a member of FKBPs family and plays a key role in various cellular processes, including signalling transduction, embryonic development and apoptosis. In order to explore the role of SQSTM1/p62 gene in cell-cycle progression and proliferation of goat foetal fibroblast (GFbs), SQSTM1/p62 gene was cloned and characterized. Furthermore, the yeast two-hybrid screening system was used to identify the interaction between SQSTM1/p62 and FKBP38. The results suggested that SQSTM1/p62 directly interacts with FKBP38. Overexpression vector pIRES-EGFP-SQSTM1/p62 and shRNA eukaryotic expression vector pRNAT-U6.1-shSQSTM1/p62 which harboured siRNA targeting the SQSTM1/p62 mRNA were constructed. The overexpression of SQSTM1/p62 gene in GFbs significantly increase the S-phase cells compared with control cells ( p  < .05). Furthermore, SQSTM1/p62 gene silencing in GFbs leads to a significant decrease of S-phase cells and cell cycle arrest compared with control cells ( p  < .05). These data indicate that SQSTM1/p62 gene plays an important role in cell-cycle and proliferation of Cashmere GFbs. Abbreviations: Aba: aureobasidin A; EIF1: eukaryotic translation initiation factor 1; FKBP: FK506-binding protein; FKBP38: FK506-binding protein 38; GFbs: goat foetal fibroblast; mTOR: mammalian target of rapamycin; PDLIM7: PDZ and LIM domain 7; SD: standard dropout; SQSTM1/p62: sequestosome 1